Il lavoro dopo il Novecento: da produttori ad attori sociali La città del lavoro di Bruno Trentin per un'«altra sinistra» - Gramolati, Alessio; Mari, Giovanni (Studi e saggi, 2016)
This volume, born from the collaboration of thirty-four scholars and trade union representatives, has a dual purpose. Firstly, to propose the analysis and theses on the human and political meaning of work contained in Bruno Trentin's main book La città del lavoro (2nd ed., Firenze University Press, 2014), in the current phase of social transformations and theoretical uncertainties. Secondly, to promote a reflection testing the book's fertility and topicality in order to deepen the processes at work at the start of the 21st century, in the belief that the pages written in 1997 by one of the greatest representatives of the history of the CGIL represent a 'classic' of the socio-political thought of the 20th century. The emerging result is surprising in many ways, and corresponds to the extraordinary richness of Trentin's project, as well as to the political and trade-unionist ability of its author. TUESDAY, MAY 17 Sede Nazionale della CGIL (Sala Santi) - Corso d'Italia 25 - Rome Presentation of the book "Bruno Trentin e il lavoro dopo il Novecento